Analisis Pengaruh Current Ratio, Total Asset Turnover, Return on Asset dan Debt to Equity Ratio Terhadap Financial Distress - Iffa Karimah; Agus Sukarno (Jurnal Ilmiah Manajemen Kesatuan, 2023)
This study aims to determine and analyze the effect of Current Ratio (CR), Total Asset Turnover (TATO), Return on Assets (ROA), and Debt to Equity Ratio (DER) on Financial Distress in Automotive and Component companies listed on the Indonesia Stock Exchange (IDX) 2018-2021. The population in this study are Automotive and Component companies listed on the Indonesia Stock Exchange (IDX) in 2018-2021. The sampling technique used purposive sampling and obtained a sample of 12 companies according to the research criteria. The analysis technique used is multiple regression analysis. The results of hypothesis testing show that the Current Ratio (CR), Total Asset Turnover (TATO) and Return on Assets (ROA) have no effect on Financial Distress, while the Debt to Equity Ratio (DER) has a positive and significant effect on Financial Distress.